Monetary Policy and Its Role in Promoting a Circular Economy in Iraq - Husham Sabeeh Zayer (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The transition from a linear to a circular economy has become essential for sustainable resource management and environmental protection, particularly in developing economies. Specific Background: In Iraq, monetary policy implemented by the Central Bank plays a role in supporting circular economy initiatives through non-traditional instruments such as Special Drawing Rights, green quantitative easing, and carbon emission reduction certificates. Knowledge Gap: Despite the availability of these tools, limited empirical evidence exists on their role in advancing circular economy practices within the Iraqi context. Aims: This study aims to examine the role of unconventional monetary policy tools in promoting the transition to a circular economy in Iraq. Results: Using a descriptive-analytical approach and questionnaire data from 69 entrepreneurs analyzed via SPSS, the findings reveal strong positive relationships between Special Drawing Rights (R²=55.2%), green quantitative easing (R²=70.3%), and carbon emission reduction certificates (R²=42.3%) with circular economy promotion. Novelty: The study provides empirical validation of integrating smart monetary instruments within circular economy frameworks in a developing country context. Implications: The findings suggest that activating non-traditional monetary tools can support financial stability, diversify the economy, reduce dependence on oil revenues, and facilitate sustainable development strategies in Iraq. Highlights:• Strong Correlations Identified Between Unconventional Financial Instruments and Circular System Adoption• Green Quantitative Easing Shows Highest Explanatory Power Among Examined Variables• Carbon Certificates and Reserve Assets Linked With Investment in Low-Carbon Projects Keywords: Monetary Policy, Circular Economy, Special Drawing Rights, Green Quantitative Easing, Carbon Emission Certificates.